Readings in deviant behavior - Terrell, Nathaniel E. (Harcourt College Publishers, 2001)
READINGS IN DEVIANT BEHAVIOR: CLASSIC AND CONTEMPORARY brings together over 50 articles in 16 chapters. The text is organized traditionally, beginning with a discussion on the nature of deviance followed by material on theories and perspectives to explain deviance and ending with articles that discuss forms of deviant behavior. Each chapter begins with an introduction and concludes with questions for discussion. The mix of contemporary and classic readings explores the theoretical approaches to deviant and contemporary issues. High-tech, white-collar crime and gender issues are included. This text parallels the organization of the best-selling Clinard/Meier text but is general enough to be used with other textbooks or as a stand-alone textbook